A comparison of isomaltulose versus maltodextrin ingestion during soccer-specific exercise - Stevenson, E. J.; Watson, A.; Theis, S.; Holz, A.; Harper, L. D.; Russell, M. (European Journal of Applied Physiology, 2017)
Purpose: The performance and physiological effects of isomaltulose and maltodextrin consumed intermittently during prolonged soccer-specific exercise were investigated. Methods: University soccer players (n = 22) performed 120 min of intermittent exercise while consuming 8% carbohydrate-electrolyte drinks (equivalent to ~ 20 g h-1) containing maltodextrin (Glycaemic Index: 90-100), isomaltulose (Glycaemic Index: 32) or a carbohydrate-energy-free placebo in a manner replicating the practices of soccer players (i.e., during warm-up and half-time). Physical (sprinting, jumping) and technical (shooting, dribbling) performance was assessed. Results: Blood glucose and plasma insulin (both P < 0.001) concentrations varied by trial with isomaltulose maintaining > 13% higher blood glucose concentrations between 75 and 90 min versus maltodextrin (P < 0.05). A decline in glycaemia at 60 min in maltodextrin was attenuated with isomaltulose (-19 versus -4%; P = 0.015). Carbohydrates attenuated elevations in plasma epinephrine concentrations (P < 0.05), but isomaltulose proved most effective at 90 and 120 min. Carbohydrates did not attenuate IL-6 increases or reductions in physical or technical performances (all P > 0.05). Ratings of abdominal discomfort were influenced by trial (P < 0.05) with lower values for both carbohydrates compared to PLA from 60 min onwards. Conclusions: Although carbohydrates (~ 20 g h-1) did not attenuate performance reductions throughout prolonged soccer-specific exercise, isomaltulose maintained higher blood glucose at 75-90 min, lessened the magnitude of the exercise-induced rebound glycaemic response and attenuated epinephrine increases whilst maintaining similar abdominal discomfort values relative to maltodextrin. When limited opportunities exist to consume carbohydrates on competition-day, low-glycaemic isomaltulose may offer an alternative nutritional strategy for exercising soccer players.